2007
DOI: 10.1080/07434610601180026
|View full text |Cite
|
Sign up to set email alerts
|

The Swedish speech interpretation service: An exploratory study of a new communication support provided to people with aphasia

Abstract: Until recently, people with complex communication needs have had no access to professional interpreters. The Swedish Speech Interpretation Service (SSIS) is attempting to address this problem. This qualitative study reports on how 12 persons with aphasia experienced the services of a professional interpreter from the SSIS. The results are presented in two themes: (a) The purpose of using an interpreter, which addresses issues relating to autonomy, privacy, and burden on family members; and (b) perceptions of q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Having medical centers or other organizations provide other advocates trained in communication disorders who could assist in providing communication support during healthcare encounters might be a beneficial alternative, and should be factored into the costs of communication accommodations. 69 70…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Having medical centers or other organizations provide other advocates trained in communication disorders who could assist in providing communication support during healthcare encounters might be a beneficial alternative, and should be factored into the costs of communication accommodations. 69 70…”
Section: Discussionmentioning
confidence: 99%
“…Having medical centers or other organizations provide other advocates trained in communication disorders who could assist in providing communication support during healthcare encounters might be a beneficial alternative, and should be factored into the costs of communication accommodations. 69,70 Use of Online Health Portals and Information This study revealed a low rate of utilizing online options for healthcare communication. An important reminder is that these data were collected prior to the COVID pandemic.…”
Section: Availability Of Communication Help During Medical Encountersmentioning
confidence: 93%
“…Higashi et al (2007) investigated the association between verbal communication and subjective well-being among Japanese elderly residents of rural communities, and reported that the frequent satisfaction derived from verbal communication with families or other rural residents improved their subjective well-being. In the case of aphasia patients, who face difficulties with verbal communication, conversational support from volunteers or professional interpreters trained in communication skills improved the patient's satisfaction with their communication, as well as providing them with more frequent opportunities for communication (Suzuki, 2012;Larsson & Thoren-Jonsson, 2007). These reports indicated that richness in communication opportunities or smooth communication exchanges improved individual's satisfaction with communication, as well as their subjective wellbeing.…”
Section: Introductionmentioning
confidence: 99%